Integrative and Disintegrative Media Functions in the Information Society - Łęcicki, Grzegorz (Žurnalistikos tyrimai, 2011)
The article aims to analyse the technological as well as ideological factors enabling integrative or disintegrative media role in society. The main assumption focuses on the social dimension of communication. The article states that internet should follow the media mission and preserve moral values. The conclusion is made that Catholic Church media doctrine seems quite effective and may be proposed as opposition to media liberalism that leads to destruction of responsible individuals, nations, and cultures.Keywords: Catholic Church media doctrine, community, disintegration, ethics, function, integration, mass media, role, social communication, social media, value.